Effects of e-banking on growth of customer base in kenyan banks - Bichanga Walter Okibo; Ali Yattani Wario (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
The study highlights the effects of E-banking services on growth of customer base in Kenyan banks for over the last five years. It addresses issues that affect effective utilization of E-banking facilities by customers. The study generally investigates how lack of technological know-how, illiteracy, unreliability, and transaction limits has hindered growth of on-line customer base in Kenyan banks. E-banking provides enormous benefits to consumers in terms of time saving and cost of transactions, either through internet, telephone or other electronic delivery channels. The research adopted a descriptive research design, to survey of selected Kenyan banks. The study used stratified random sample to ensure equal representation where 135 respondents who were selected from the strata/ banks. According to the results obtained in the study e-banking has enhanced the growth of the customer base for the banking institutions in Kenya, through enhancing banking services accessibility to a larger population in the country. Therefore the study recommended that the banks should embrace e-banking as a key competitive advantage.
Keywords: 650; Electronic Banking; Innovation; Internet Banking and Customer Base